Loss Aversion and Tax Evasion: Theory and Evidence - Sanjit Dhami; Narges Hajimoladarvish; Pavan Mamidi (Center for Economic Studies and ifo Institute (CESifo), 2023)
We consider income-source-dependent tax evasion and show that this is a generalization of the well-known endowment effect. We show that loss aversion, moral costs, mental accounting, and risk preferences play a key role in explaining key features of source-dependent tax evasion. We provide evidence of the first direct link between subject-specific loss aversion and tax evasion, which is central to most successful modern theoretical accounts of tax evasion. We provide some evidence that risk aversion strengthens the cautionary effect of loss aversion and risk loving behavior attenuates, or reverses, it. However, the underlying effect is also influenced by the source of income. Evasion is increasing in the tax rate and decreasing in the audit penalty, as predicted. Our paper provides novel theoretical insights; proposes new methods in the estimation of the underlying behavioral parameters; and confirms the central predictions of the theory, while pointing out challenges for further developments that existing theory is unable to account for.
Keywords: C91; C92; D82; D91; G21; 330; tax evasion; endowment effect; loss aversion; morality; mental accounting; prospect theory; risk aversion